JOINT INVOLVEMENT IN SYPHILIS - T. I. Zlobina; A. A. Melnikova; A. N. Kalyagin (Современная ревматология, 2016)
Joint involvement in syphilis has been considered as casuistry in recent years. At the same time, the high incidence of primary syphilis and the notified cases of late neurosyphilis may suggest that joint involvement in this disease is by no means always verified. Traditionally there are two forms of syphilitic arthritis: primary synovial (involving the articular membranes and sac) and primary bone (involving the articular bones and cartilages) ones. The paper describes the authors' clinical case of the primary bone form of articular syphilis in a 34-year-old man.